Dilemma Executive Control: Development of Regional Regulatory Canceling Models - Sonia Ivana Barus (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The Law Number 23 of 2014 concerning Regional Government clearly states that the Minister of Home Affairs with instruments in the form of a Ministerial decree bears the authority to annul regional regulations which deemed contrary to the provisions of the higher laws, public interests and/or decency. However, the Constitutional Court (MK) through Decision No. 137/PUU-XIII/2015 and MK’s Decision No. 56/PUU-XIII/2016 has restrained the authority of the Minister of Home Affairs to annul the Regional Regulation (perda). This is an interesting discussion, some consider that it actually weakens the role of the central government to control local governments, on the other hand, justifying that authority belongs to the Supreme Court. Interesting problems of this research is what is the actual relations of authority between local and central government? Then what is the ideal model for the annulment of regional regulations so that the central government has a role in exercising control (executive control) of regional regulations before and after regional regulations come to be applied? This research was conducted using a normative juridical method, namely a research method that refers to the norms of legal norms contained in statutory regulations. This research resulted that there is a decentralization and decencentration relationship between the central and local governments. In order to anticipate these problems, the ideal model for cancellation of regional regulations to accommodate the authority of the central government is to separate regional regulation according to the content or material